The Effect Of Training, Career Development And Work Motivation On Employee Performance With Job Satisfaction As An Intervening Variable In Pt Weltes Energi Nusantara - Mayumi Clodya Saragih; M. Chaerul Rizky (Yayasan Multidimensi Kreatif, 2025)
This research is entitled The Influence of Training, Career Development and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable at PT Weltes Energi Nusantara. The purpose of this study is to analyze how training, career development, and work motivation simultaneously and partially affect employee performance, as well as the role of job satisfaction as an intervening variable in the relationship. The method used in this study is a quantitative approach with a survey design. Data was collected through a questionnaire distributed to employees of PT Weltes Energi Nusantara. Data analysis was carried out using multiple linear regression to test the hypothesis proposed and processed with SPSS software version 29.0. The results of the study show that training, career development, and work motivation each have a positive and significant influence on job satisfaction and employee performance directly. Job satisfaction has also been proven to have a significant effect on employee performance. In the mediation effect analysis, it was found that training did not have a significant influence on employee performance through job satisfaction as an intervening variable. However, career development and job motivation are proven to have a significant influence on employee performance through job satisfaction as an intervening variable. These findings indicate that a good career development program and high job motivation can effectively improve employee performance through increased job satisfaction, while the influence of training on performance is more effective directly without mediating job satisfaction.